2022
DOI: 10.3389/fpubh.2022.1051754
|View full text |Cite
|
Sign up to set email alerts
|

Method comparison for Japanese encephalitis virus detection in samples collected from the Indo-Pacific region

Abstract: IntroductionJapanese encephalitis virus (JEV) is a mosquito-borne viral pathogen, which is becoming a growing public health concern throughout the Indo-Pacific. Five genotypes of JEV have been identified. Current vaccines are based on genotype III and provide a high degree of protection for four of the five known genotypes.MethodsRT-PCR, Magpix, Twist Biosciences Comprehensive Viral Research Panel (CVRP), and SISPA methods were used to detect JEV from mosquito samples collected in South Korea during 2021. Thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Here, we have demonstrated the effectiveness of target capture sequencing directly from respiratory clinical specimens with low viral load. The capture panel, the Twist Comprehensive Viral Research Panel, was selected for its ability to capture a very wide range of viral pathogens; to our knowledge, this is the first evaluation using human respiratory clinical specimens with low viral load although the panel has been used on human cerebrospinal fluid (26), saliva, blood and feces from wild bats (27) and mosquito samples (28). Target capture sequencing with this panel yielded approximately 180- and 2000-fold higher read counts of SARS-CoV-2 or influenza A virus, respectively, than metagenomic sequencing when RNA extracts from specimens containing 59.3 or 544 RNA copies/µL of SARS-CoV-2 or influenza A virus were used, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have demonstrated the effectiveness of target capture sequencing directly from respiratory clinical specimens with low viral load. The capture panel, the Twist Comprehensive Viral Research Panel, was selected for its ability to capture a very wide range of viral pathogens; to our knowledge, this is the first evaluation using human respiratory clinical specimens with low viral load although the panel has been used on human cerebrospinal fluid (26), saliva, blood and feces from wild bats (27) and mosquito samples (28). Target capture sequencing with this panel yielded approximately 180- and 2000-fold higher read counts of SARS-CoV-2 or influenza A virus, respectively, than metagenomic sequencing when RNA extracts from specimens containing 59.3 or 544 RNA copies/µL of SARS-CoV-2 or influenza A virus were used, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In 17 cases, AAV2 was detected using targeted sequencing, while in seven of these pediatric cases AAV2 was missed by untargeted metagenomic sequencing, illustrating the significance of the use of enrichment by hybridization. With regard to costefficiency, a recent study compared PCR, sequence-independent single primer amplification (SISPA), and the Twist Comprehensive Viral Research Panel for the detection of Japanese encephalitis 44 . The authors concluded that the PCR panels were not able to detect all genotypes, whereas broader surveillance of vector-borne pathogens would be more effective though costly 44 .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to costefficiency, a recent study compared PCR, sequence-independent single primer amplification (SISPA), and the Twist Comprehensive Viral Research Panel for the detection of Japanese encephalitis 44 . The authors concluded that the PCR panels were not able to detect all genotypes, whereas broader surveillance of vector-borne pathogens would be more effective though costly 44 . Hybridization capture has been approved by the FDA for SARS-CoV-2 variant monitoring, illustrating the acknowledged significance of this type of enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Samples from confirmed cases with acute infection were processed to obtain the whole genome by a target enrichment standard hybridization workflow using the Twist Biosciences Comprehensive Viral Research Panel (CVRP), comprising approximately one million 120-base pair probes designed to target 15,488 distinct viral strains that infect both humans and animals, as previously described [ 14 ]. Briefly, extracted RNA samples were used as a template for a reverse transcription step with the SuperScript IV Reverse Transcriptase kit (Invitrogen, Thermo Fisher, USA) followed by a DNA fragmentation, telomere repair, dA-Tailing and a ligation with Universal Twist adapters before a final libraries amplification.…”
Section: Methodsmentioning
confidence: 99%